The art of honing the conscience through bukalapak ads: barongsai Indonesia, juara hati membangun bangsa - Andreas Lumampauw; Rustono Farady Marta; Yohanes Nugroho Widyanto; Todd Lyle Sandel; Sunny Lie (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2021)
Culture is one of the foundations for the existence of Indonesia as a nation, as it is expressed in the second stanza of her national anthem. The government has taken an initiative to prioritize national character building, which places character education to realize the vision of national development. One of the efforts to visualize this Indonesian is constructed through a Bukalapak advertisement entitled “Barongsai Indonesia, Juara Hati Membangun Negeri,” which presented the Kong Ha Hong lion dance group and was published via Youtube. This study aims to see that the character values of the Indonesian nation can be constructed through digital media, more precisely through an advertisement. This research employed a qualitative approach with a constructivist paradigm that sees facts as unique and has a special meaning. In addition, the analysis used Thomas Albert Sebeok's visual semiotics to depict several similar classifications to different visual symbols. It was found that every advertisement scene contained both visual and audio messages related to the adaptation of the culture and character of the Indonesian. The contribution and novelty of this research in its construction of the deep meaning of an advertisement are that the conscience has played a major role in the process of cultural adaptation in which the national characters have been honed through the actual actions in the heart-mind, body, and spirit. This research suggested that the character of the Indonesian nation can be formed through cultural adaptation, as proven by the Kong Ha Hong lion dance